Evaluating Nursing Students' Understanding of Hydatid Disease in Iraq: Mengevaluasi Pemahaman Mahasiswa Keperawatan tentang Penyakit Hidatidosa di Irak - Husham Hussain Abdul Ra’aoof (Academia Open, 2024)
This study investigates the knowledge, attitudes, and awareness regarding Hydatid Disease among Nursing College students at the University of Basrah, recognizing its status as a neglected zoonotic disease. Utilizing a descriptive cross-sectional questionnaire-based approach, data were collected from 380 male and female students across the 2nd, 3rd, and 4th stages of study. Results reveal a significant lack of knowledge, with over half of the participants demonstrating poor understanding of the disease. Only a small fraction exhibited good knowledge, emphasizing the urgent need for heightened awareness initiatives. Interestingly, older students showed slightly better attitudes compared to younger ones. These findings underscore the necessity for targeted educational interventions to improve knowledge and attitudes toward Hydatid Disease among nursing students, ultimately enhancing public health outcomes. Highlights: Significant lack of knowledge among Nursing College students regarding Hydatid Disease. Urgent need for heightened awareness initiatives to address the knowledge gap. Targeted educational interventions required to improve attitudes and knowledge among students. Keywords: Hydatid Disease, Nursing College Students, Awareness, Knowledge, Attitude